Pengaruh Lingkungan Kerja dan Motivasi Kerjaterhadap Kinerja Karyawan Cv Utama Sejahtera Motor - Filhafi Fahira Rahman; Wike Pertiwi; Maman Mulya Karnama (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the influence of the work environment and work motivation on employee performance at CV Utama Sejahtera Motor. The research method used is a quantitative approach with descriptive and verification analysis. The study population included 149 employees, with a simple random sample of 108 respondents. Data were analyzed using multiple linear regression using SPSS software. The results indicate that work motivation has a positive and significant effect on employee performance, while the work environment does not show a significant effect partially. Simultaneously, both variables have a positive and significant effect on employee performance. The conclusion of this study is that work motivation plays a stronger role in improving employee performance than the work environment, although both can improve employee performance together. Keywords: Work Environment, Work Motivation, Employee Performance, Influence